Multisensory Marketing: Creating Sustainability Perspective in Various Sectors. (March 2014) - Kumar, Prarthana
Synchronic studies in marketing propose that sensory stimulus, like colour, lighting effects, backdrop music, ambient scents or upholstery's texture, affect consumers' evaluation of the milieu, the wares presented and affect consumer behaviour (e.g., approximate amount spent, time spent at a store). A customer is frequently attracted towards a brand based on its sensory experience. In toto, the unexpurgated world is experienced through multiple senses (Lindstrom, 2005b ). Ingenious brands are discovering means to captivate the entire consumer senses to fortify their brand experience, by amalgamating every sense into the marketing strategy; this approach is called 'sensory marketing'. Sensory branding is based on the idea that we are most likely to form, retain and revisit memory when all five senses are engaged. Many companies are discovering that when they engage consumers with multiple sensory touch points—not just the traditional sensory channels of sight or hearing—they can enhance customers' emotional connection with their products and brands. The multisensory strategies seek to go beyond delivering functionality and value to evoking significant personal identification with products. It aims to fill in the lacuna of the conventional marketing. Technology is one of the main factors driving sensory marketing to success. Sensory marketing has made its mark in multiple fields like automobiles, airlines, hospitality, casinos, retail stores, textile, leather production, skin care and cosmetics at multiple levels. The following are a few examples for multisensory applications: 74 per cent of Europeans and 46 per cent of American recognise the Nokia ringtone (Lindstrom, 2005a ); Ford has a specific branded aroma since 2000. Twenty seven per cent of US consumers and 37 per cent of Europeans consider ford has a distinct smell (Lindstrom, 2005a ); United Airlines has adapted a famous composition, George Gershwin's Rhapsody in Blue, and personalised it; Restaurants play slower music as it creates extended dining hours, increasing 29 per cent of average bill according to an experiment; Heinz launched EZ Squirt Blastin', Green Ketchup in 2001. They sold over 10 million bottles in the first seven months. That is the highest sales peak in the history of Heinz, all because of a simple colour adjustment. This article deals with use of sensory marketing in various sectors and its potential to develop as a sustainability strategy.